Formulation and Evaluation of Transdermal Patches for Antianxiety Drug (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim of the present study was to design, develop, and evaluate a matrix-type transdermal formulationcontaining buspirone hydrochloride (HCL) for treatment of anxiety with a goal to increase the bioavailability andimprove the patient compliance. Materials and Methods: In the present research work, the different concentrationsof hydroxypropyl methylcellulose (HPMC) E50, HPMC E15, and Eudragit RS100 were used in combination tooptimize the concentration of HPMC E15 and Eudragit RS100 in the formulation of transdermal patches. Thesedifferent ratios of hydrophilic and hydrophobic polymeric combinations plasticized with dibutyl phthalate by thesolvent evaporation technique. The prepared patches were evaluated for their physicochemical characteristics suchas thickness, weight and drug content uniformity, moisture content, moisture uptake and folding endurance, andin vitro drug release studies. Optimized formulation was further evaluated by in vivo release study, drug-excipientcompatibility, and stability study. Results and Discussion: Effect of permeation enhancers such as oleic acid wasstudied. The interference of the polymers was ruled out by Fourier transform infrared and ultraviolet-spectroscopicmethods. In vitro release studies of buspirone HCL-loaded patches in phosphate buffer (pH, 7.4) were performedusing a modified diffusion cell and showed first-order release rate. Skin studies for the transdermal patches wereassessed and were found to be free of irritation. In vivo drug release studies had shown release up to 24 h with therelease of 73.82% and it was correlated with in vitro studies. The patches were subjected to short-term stabilitystudies and were found stable. Conclusion: It is concluded from the present studies that the transdermal patchesof buspirone HCL were capable of exhibiting controlled release with the stability. Studies had shown promisingresults, and there was a scope for further pharmacodynamic and pharmacokinetic evaluation.